Investors Perception on Civil Remedies and Civil Action under the Capital Markets and Services Act 2007 - Yeon, Asmah Laili; Yaacob, Nurli (International Journal of Economics and Financial Issues, 2016)
The Capital Markets and Services Act 2007 provides civil action and remedies for the victim of securities crimes. Whether these remedies are sufficient to protect investors' interest when dealing in securities transaction is an issue to be discussed in the paper? This paper aims to analyze investors' perception on civil remedies and action. This paper based on the legal research findings where a systematic method of exploring, investigating, analyzing and conceptualizing legal issues pertaining to the enforcement mechanisms and implication of the legal rules and principles. It involves systematic, inquiry or investigation of the factual data and theoretical concepts of the rules and principles of investors' compensation scheme of capital markets and services in Malaysia. The findings of the research shows that legal provisions of capital markets compensation fund is fairly sufficient and presumably can protect investors in the securities market. However, the Corporation should exercise more care and diligence in exercising their duties and responsibilities in managing the fund. The power given by the law to the Corporation is so wide. The researchers are of opinion the Corporation had an extensive power to invest but it is paramount important to balance ratios/portions of fund monies according to priority of the fund purposes. Keywords: Capital Markets Law, Civil Action, Civil Remedies, Investors Protection JEL Classifications: C33, F11, N50